Família e escola: o contraponto em Helena Antipoff através da correspondência com o filho Daniel (1929-1938) - Sérgio Faleiro Farnese (2023)
This dissertation aims to present the history of the separation that the psychologist and educator Helena Antipoff entertained with her only child, Daniel, by educating him through weekly letters between her and him for nine years, from 1929 to 1938. The theoretical framework used to work on this extensive correspondence performs a kind of phenomenology suggested by Husserl, added to the care that the critiques of Kant and Marx postulate for theoretical activity, also taking into account consideration of the epistolary literature of the last centuries, such as the recent publications of letters between Claparède and Antipoff and those of Freud to his childrens. As for the method, after a longitudinal reading of the approximately 700 letters, ordered chronologically, we selected 59 from Helena Antipoff, distributed in three frames (of Daniel's childhood, adolescence and youth), scrutinized by the themes dealt with, and then we present some of them. We consider that the results obtained offer scholars an overview of the content and relevance of this collection for the treatment of counterpoint relations - from the school - to the limitations of the family, because they refer us to the best of philosophy, psychology and pedagogy of all times for completing the educational task. On this landing, a tripod was erected: the creation of a new school, in Beauvallon, France, weekly letters and scouting, with the varnish of musicality. The coups d'état in Brazil (1930 and 1937) and the rise of Nazism in Europe, involve the lyrical and philosophical content of the letters, which became living testimony of those historical moments. In turn, the then recent educational action of Antipoff, in Russia in the early years of revolution of 1917, is revealed in writing in an informal translation of her doubts and convictions. The insistent invitations to the son to join her in caring for the youth imprisoned by the prison system in Minas Gerais indicate, in those years of separation, his inclination towards the paths of inclusive education, the keynote of her masterful work. As a conclusion, we consider that our effort brought to light - as an invitation - a passionate option for the art of living and the art to educate, suggested in that voluntary separation between mother and child for almost half a thousand weeks, united by the delicate and intimate bond of the same number of letters from sea to sea.